Drama of O. P. Chugui: A staging of the play "The Cathedral" by O. Honchar - Телехова, Олександра Петрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article analyzes the quality of the translation of the epic composition to the dramatic, degree of preservation by the author of the dramatization of the ideological and artistic content of the novel by one of the most prominent writers of the second half of the twentieth century. It is noted that the drama "The Unconquered Cathedral" is the most adequate epic canvas of O. Gonchar and at the same time fully corresponds to the requirements of dramatic poetics, because the author managed to convey the problems and deep ideological content of the novel, a feature created by the prose writer of many-sided characters, the greatness and beauty of the Ukrainian language. O. Honchar focused on the Cossack cathedral, which was located on the territory of the Dnipropetrovsk region and was kept as an architectural monument, undergoing constant attempts to liquidate officials, despite local residents’ protests. The novel was called the "Cathedral" and, of course, could not but attract the attention of the theater figures. However the "Cathedral" staging was made possible only after Ukraine gained independence. However, note that the novel classic of Ukrainian literature nevertheless is a typical epic product, which consists of 26 sections covering 270 pages. It is dominated by a detailed story, whose dialogues make up only 15 percent of the total volume, which is clearly not enough to create a full-fledged screenplay. In our opinion, the author of the screenwriting successfully coped with this task. His dialogues meet all the requirements of the dramatic genre. They are an expressive verbal fight, and not the usual conversation of actors, which is often found in prose writings. In the novel, O. Gonchar, they, though not much of a place, are basically dramatic. That is why almost all of them are carefully transferred to staging.